Measurements of the Exerted Pressure by Pelvic Circumferential Compression Devices - Knops, Simon P (Bentham Open, 2010)
BACKGROUND: Data on the efficacy and safety of non-invasive Pelvic Circumferential Compression Devices (PCCDs) is limited. Tissue damage may occur if a continuous pressure on the skin exceeding 9.3 kPa is sustained for more than two or three hours. The aim of this study was to gain insight into the pressure build-up at the interface, by measuring the PCCD-induced pressure when applying pulling forces to three different PCCDs (Pelvic Binder(®) , SAM-Sling (®) and T-POD(®) ) in a simplified model. METHODS: The resulting exerted pressures were measured at four ‘anatomical’ locations (right, left, posterior and anterior) in a model using a pressure measurement system consisting of pressure cuffs. RESULTS: The exerted pressure varied substantially between the locations as well as between the PCCDs. Maximum pressures ranged from 18.9-23.3 kPa and from 19.2-27.5 kPa at the right location and left location, respectively. Pressures at the posterior location stayed below 18 kPa. At the anterior location pressures varied markedly between the different PCCDs. CONCLUSION: The circumferential compression by the different PCCDs showed high pressures measured at the four locations using a simplified model. Difference in design and functional characteristics of the PCCDs resulted in different pressure build-up at the four locations. When following the manufacturer’s instructions, the exerted pressure of all three PCCDs tested exceeded the tissue damaging level (9.3 kPa). In case of prolonged use in a clinical situation this might put patients at risk for developing tissue damage.